Объясните,
выражение
а^5/3 * а^1/3/∛а^2 * ∛а выберите один ответ:
a^-1
a
a^2
a^0,5

kovalvladislavoxx9e6 kovalvladislavoxx9e6    3   28.11.2019 09:26    19

Ответы
dilnoza2006 dilnoza2006  10.10.2020 16:40

a

Объяснение:

(a^5/3 *a^1/3)  / (∛a² *∛a) =  a² / (a² / (3*a^1/3)=   a²/a= a

ПОКАЗАТЬ ОТВЕТЫ
Zarinochka1998 Zarinochka1998  10.10.2020 16:40

(а^5/3) * (а^1/3)/(∛(а^2) * ∛а) =(а^5/3) * (а^1/3)/((а^(2/3) * (а^(1/3))=

=(а^5/3) * (а^1/3)/a=(а^5/3) * (а^1/3)*a^(-1)=(a^5/3) * (a^(-2/3))=a^(3/3)=a

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра